2018
DOI: 10.1007/s11244-018-0900-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Carboxylation of 1-Decene to 1,2-Decylene Carbonate

Abstract: Cyclic carbonates are valuable chemicals for the chemical industry and thus, their efficient synthesis is essential. Commonly, cyclic carbonates are synthesised in a two-step process involving the epoxidation of an alkene and a subsequent carboxylation to the cyclic carbonate. To couple both steps into a direct oxidative carboxylation reaction would be desired from an economical view point since additional work-up procedures can be avoided. Furthermore, the efficient sequestration of CO 2 , a major greenhouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In 2018, Hutchings and co-workers described a one-pot, twostep sequential reaction for the synthesis of 1,2-decylene carbonate. 50 The strategy consisted of the epoxidation of 1decene in the presence of SiO 2 -supported gold catalyst under an air atmosphere and cycloaddition of CO 2 (20 atm) with the formed epoxide using TBAB and ZnBr 2 . The single-step version of this reaction was also investigated.…”
Section: Electrocatalytic Reactionsmentioning
confidence: 99%
“…In 2018, Hutchings and co-workers described a one-pot, twostep sequential reaction for the synthesis of 1,2-decylene carbonate. 50 The strategy consisted of the epoxidation of 1decene in the presence of SiO 2 -supported gold catalyst under an air atmosphere and cycloaddition of CO 2 (20 atm) with the formed epoxide using TBAB and ZnBr 2 . The single-step version of this reaction was also investigated.…”
Section: Electrocatalytic Reactionsmentioning
confidence: 99%
“…The characteristics of the support frequently influence catalyst activity. A marked support effect on conversion as well as selectivity has been demonstrated by earlier work on oxidation reaction [16].…”
Section: Effect Of the Supportmentioning
confidence: 55%
“…Active component leaching in the solution is a fundamental difficulty associated with heterogeneous catalysts, especially in the liquid phase. In our previous study [16], supported cobalt catalysts have been used for epoxidation of alkene under the same reaction conditions reported in this work. the ICP AES analysis for this previous work showed that the materials were indeed leaching active components into the reaction mixture.…”
Section: Figurementioning
confidence: 99%
“…High epoxide selectivity continues to pose difficulties in the context of the epoxidation reaction. This has led to the identification and quantification of several additional by-products, which have been comprehensively detailed in earlier studies Ruthenium Catalyst for Epoxidation Reaction DOI: http://dx.doi.org/10.5772/intechopen.96466 [15,16]. When the reaction runs for 24 hours, it results in the formation of substantial amounts of allylic products.…”
Section: Supported Ruthenium Catalysts For Epoxidation Of Alkenesmentioning
confidence: 99%